BIODEGRADATION OF SOME ENVIRONMENTAL POLLUTANTS BY LACCASE PRODUCED FROM TRICHODERMA HARZIANUM USING SOLID STATE FERMENTATION - I., Sura N.; Hashim, A. J.; Abood, W. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Trichoderma harzianum produced 5.383 U/mg of laccase in solid state fermentation (SSF) using 10gm of wheat bran as substrate with moisture content 1:0.7 w/v, using 4 plugs×5mm as inoculums size, for 7 days at 28C°. Laccase was partially purified with 7.260 fold and yield 84.01% by ion exchange chromatography DEAE-cellulose. Partially purified laccase had an optimum pH of 4 and was stable in pH range from 3.5 to 5.5. The optimum temperature for laccase activity was 35C° and stability was range from 15 to 35C° with 1h of incubation. The ability of T. harzianum isolate to decolorize textile dyes on solid media appears completely decolorization of Blue dye with concentrations 50,100 and partially decolorized with concentration 150,200 and 250 ppm, while the Yellow dye and Red dye were completely decolorized at 50 ppm concentration. The ability of partial purified laccase to degradation of phenol was completely occurs in concentration 5, 10 but at 20, 50 and 100 ppm about 90.94%, 93.93%and 36.78% respectively, while furfural degradation at 5 and 10 ppm was about 86.84% and 68.66% respectively which detected using HPLC technique.